Investigating the correlation between organizational cynicism and teacher burnout: an evidence from TRNC secondary public school teachers - Karaman, Bahar; Altınay, Zehra; Altinay, Fahriye; Dagli, Gokmen; Shadiev, Rustam; Suiçmez, İslam (Frontiers in Psychology, 2025)
This study aimed to explore the correlations between organizational cynicism, burnout, and socio-demographic variables. The sample consisted of 553 Turkish Republic of Northern Cyprus (TRNC) secondary public-school teachers. The Maslach Burnout Inventory, and the Organizational Cynicism Scale, were employed to obtain data from the participants. Results demonstrated that the cognitive and reduced personal accomplishment dimensions had the highest mean scores. Furthermore, all socio-demographic variables were correlated with burnout among the participating teachers. Conversely, organizational cynicism revealed statistically significant differences and correlations with gender, education level, and seniority variables. Spearman’s rank correlation revealed a significant and positive relationship between the two constructs, with a small-to-moderate effect size. Additionally, a simple linear test indicated that organizational cynicism had a significant and positive impact on burnout, explaining 9.9% of the total variance. Although the predictive power is limited, the findings suggest that interventions targeting cynical attitudes in school environments may help to mitigate burnout among teachers. Also organizational cynicism was also linked to seniority and educational level, indicating that tailored professional support and school-based climate interventions may be necessary for different teacher groups to prevent the escalation of burnout.